Are the unreamed nails indicated in diaphyseal fractures of the lower extremity? A biomechanical study. (July 2021) - Albareda, J.; Ibarz, E.; Mateo, J.; Suñer, S.; Lozano, C.; Gómez, J.; Redondo, B.; Torres, A.; Herrera, A.; Gracia, L.
Highlights: Biomechanical behavior of femoral and tibial fractures depends on nailing type (reamed or unreamed). Stability in the immediately post-operative is essential for fracture consolidation. Osteosynthesis stability is clearly lesser in the case of unreamed nailing compared with reamed nailing. Unreamed nailing of the femur is not a good indication even in less complex fractures. Unreamed nailing should be an exceptional option in high-energy open tibial fractures with serious soft tissues damage. Abstract: Introduction: Intramedullary nailing is generally accepted as the first choice for the treatment of diaphyseal fractures of femur and tibia, with a gradual incease in the use of unreamed nails. Different studies during last years show controversial outcomes. Some authors strongly favor unreamed nailing, but most of the authors conclude that reamed nailing have proved to be more successful. Material and methods: This study simulates unreamed intramedullary nailing of four femoral and three tibial fracture types by means of Finite Element (FE) models, at early postoperative stages with a fraction of physiological loads, in order to determine whether sufficient stability is achieved, and if the extent of movements and strains at the fracture site may preclude proper consolidation. Results: The behavior observed in the different fracture models is very diverse. In the new biomechanical situation, loads are only transmitted through the intramedullary nail. Mean relative displacement values of fractures in the femoral bone range from 0.30 mm to 0.82 mm, depending on the fracture type. Mean relative displacement values of the tibial fractures lie between 0.18 and 0.62 mm, depending on the type of fracture. Concerning mean strains, for femoral fractures the maximum strains ranged between 12.7% and 42.3%. For tibial fractures the maximum strains ranged between 10.9% and 40.8%. Conclusions: The results showed that unreamed nailing provides a very limited mechanical stability, taking into account that analyzed fracture patterns correspond to simple fracture without comminution. Therefore, unreamed nailing is not a correct indication in femoral fractures and should be an exceptional indication in open tibial fractures produced by high-energy mechanism.